STUDY OF THE DYNAMICS OF SPREAD OF DEEP VEIN THROMBOSIS OF THE LOWER EXTREMITIES BY ULTRASOUND DIAGNOSTICS METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Actuality. Early detection and monitoring of such a serious pathology as deep vein thrombosis of the lower extremities (DVT) is critically important for reducing morbidity and improving the quality of life of patients. Purpose of the study was to investigate the prevalence of DVT using ultrasound diagnostics in primary care settings. Materials and methods. The study included the protocols of 4044 patients examined between 2018 and 2024. All patients underwent compression duplex ultrasound (CDUS) to diagnose venous thrombosis and assess blood flow. The protocols were divided into three groups: before the pandemic (2018-2019), during the pandemic (2020-2021), and after the pandemic (2023-2024). Results. The results showed that during the pandemic, the detection rate of DVT significantly increased from 3.9% (before the pandemic) to 15.1% (during the pandemic), while after the pandemic, this figure again decreased to 3.8%. It has been established that the frequency of DVT depends on age, gender, and symptoms. Conclusions. The COVID-19 pandemic had a significant impact on the prevalence of lower extremity deep vein thrombosis, confirming the need for regular monitoring of the state of the vessels in patients at risk of thrombosis (especially in patients with postoperative and traumatic, cardiovascular and oncological diseases). Duplex scanning remains the primary method for early detection of deep vein thrombosis in the lower extremities and improvement of clinical outcomes.